New Quenching Method for Improving Large‐Scale Stopped‐Flow Technique. Issue 11 (18th June 2014) - Thakur, Ashutosh; Poonpong, Supawadee; Terano, Minoru; Taniike, Toshiaki
Abstract The stopped‐flow (SF) technique has been extensively used for active site analyses and kinetic investigations in heterogeneous Ziegler‐Natta olefin polymerization catalysis, whereas a poor polymer yield due to a short polymerization period has been a major drawback of the conventional SF system, which later has been improved by the development of a large‐scale SF (LSF) technique. In order to further improve the scalability of the LSF technique, the present paper reports a new polymerization quenching method, which has been established by applying a three‐vessel‐type analogue of the LSF system. The new quenching method endows identical kinetic profiles, but the scalability is successfully improved.<inline-graphic xlink:href="ark:/27927/pgh24chbwhb" content-type="mren201400014-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />